Association between CAPN-10 gene variant and diabetes mellitus in Nigeria: a review - David Olufemi Adebo; Mathew Folaranmi Olaniyan; Christian Onosetale Ugege; Odekunle Bola Odegbemi (Egyptian Journal of Medical Human Genetics)
Abstract Background Type 2 Diabetes Mellitus (T2DM) is a significant global health concern characterised by insulin resistance and chronic hyperglycemia. Genetic factors, particularly variations in the CAPN-10 gene, have been implicated in T2DM susceptibility across diverse populations. Aim and objective This study aimed to conduct a meta-analysis to investigate the associations of single nucleotide polymorphisms (SNPs) in the CAPN-10 gene with T2DM among various populations, focusing specifically on Nigerian cohorts. Materials and methods A comprehensive literature search yielded 150 studies, from which 45 met inclusion criteria, encompassing approximately 25,000 individuals, including 10,000 diagnosed with T2DM. Statistical analyses assessed the association between CAPN-10 SNPs (UCSNP-43, UCSNP-19, UCSNP-63) and T2DM risk. Results A significant association was observed for UCSNP-43 (rs3792267) with T2DM (OR 1.50; 95% CI 1.28–1.75; p < 0.001), particularly in urban Nigerian populations. UCSNP-19 (rs3842570) also showed a moderate association (OR 1.35; 95% CI 1.10–1.66; p = 0.01), especially in South-West Nigeria. No significant association was found for UCSNP-63 (OR 1.15; 95% CI 0.90–1.45; p = 0.30). Conclusion The findings indicate that CAPN-10 SNPs, particularly UCSNP-43 and UCSNP-19, contribute to T2DM susceptibility in Nigerian populations, emphasising the importance of genetic screening for personalised interventions in diabetes management.